Direct Enzymatic Synthesis of 1‐Phosphatidyl‐β‐D‐glucose by Engineered Phospholipase D. Issue 13 (30th August 2016) - Inoue, Arisa; Adachi, Masaatsu; Damnjanović, Jasmina; Nakano, Hideo; Iwasaki, Yugo
Abstract: A simple, direct method for the synthesis of 1‐phosphatidyl‐β‐D‐glucose (1‐PGlc) was established, being the first example of direct enzymatic synthesis of this recently discovered, highly important bioactive phospholipid. The method employs phospholipase D (PLD, E.C. 3.1.4.4)‐catalyzed transphosphatidylation, in which the polar head group of phosphatidylcholine is exchanged to glucose. Although wild‐type PLD can catalyze the transfer reaction, it provides only 6‐phosphatidyl‐glucose, a positional isomer of 1‐PGlc, due to its strong preference towards the primary hydroxyl group. To synthesize 1‐PGlc, engineered PLD variants, previously isolated as the ones active on secondary hydroxyls of inositol, were screened for the ability to catalyze the reaction. One of the variants, 187K/191W/385Y (KWY), was identified as the best‐performing in 1‐PGlc synthesis, however, in addition to 1‐PGlc the reaction with KWY also afforded undesired positional isomers as byproducts. To facilitate the isolation of 1‐PGlc, the isomers were converted into the corresponding amines by reductive amination. Following the column chromatography, the desired product was isolated with the overall yield of 12.5 %. The structure of the product was confirmed by 1 H‐NMR analysis. Abstract : Simple synthesis of a bioactive phosphatidylglucoside: An engineered phospholipase D (PLD) with altered substrate specificity enables the synthesis of 1‐phosphatidyl‐β‐D‐glucose (1‐PGlc) from phosphatidylcholine (PC) and unprotected glucose, exclusively with β‐configuration. This synthesis cannot be performed by the wild‐type enzyme, which provides only 6‐PGlc, a positional isomer of 1‐PGlc.